Cash Flow Projection Analysis of a Defined Benefit Pension Fund Under Membership Freezing Conditions in Indonesia - Kristiani Tri Lestari; Zaäfri Ananto Husodo (Politeknik Siber Cerdika Internasional, 2026)
Background: Defined Benefit Pension Funds (DPPK PPMP) in Indonesia face funding sustainability risks as frozen membership reduces contribution inflows while long-term pension obligations persist. Objective: This study evaluates the long-term cash flow sustainability of DPPK PPMP with frozen membership, identifies key funding determinants and deficit points, and proposes mitigation strategies. Methods: A descriptive-analytical quantitative approach was applied to 18 DPPK PPMP with frozen membership using financial statements, actuarial reports, and OJK audit results from 2023–2025. Cash flows were projected through 2062 under fixed actuarial assumptions and no new participants or operational costs. Funding ratios, net cash flows, and heatmaps were analyzed. Results: Pension Funds F and P entered negative cash flow in 2027, while B, C, L, and O maintained funding ratios above 100% through 2062. Participants aged 56–75 represented 65% of membership, with retirees reaching 95% in some funds. Only four funds remained financially resilient, while the remainder faced high to very high funding risk. Sustainability was mainly determined by initial asset adequacy, participant demographics, and investment returns. Conclusion: Most DPPK PPMP with frozen membership face long-term funding deficits. Regular cash flow projections, strengthened Asset Liability Management, and funding recovery plans are essential to ensure sustainable pension payments.